A comprehensive improved coordinated control strategy for a STATCOM integrated HVDC system with enhanced steady/transient state behaviors. (October 2020) - Wang, Puyu; Wang, Yongkun; Jiang, Ningqiang; Gu, Wei
Highlights: An improved coordinated control strategy of STATCOM is proposed for enhancing steady/transient states characteristics of LCC HVDC systems. A switching control strategy of constant AC voltage control and constant reactive power control is proposed for steady states. A fast reactive power droop control with additional turn-off angle negative feedback control is proposed for transient states. The proposed control strategy has capability of fast reactive power compensation and system voltage support, mitigation of continuous commutation failures and assisting system recovery. Abstract: As a parallel type of reactive power compensation equipment, a static synchronous compensator (STATCOM) is often used to connect at the weak AC end of the inverter side of the high voltage direct current (HVDC) transmission system. In this paper, an improved coordinated control strategy of a STATCOM is investigated with three main contributions: 1) The operation modes of the STATCOM are analyzed and its steady-state mathematical model is established. The dynamic behaviors of the STATCOM under different operating conditions are studied; 2) A coordinated control strategy of the STATCOM, which takes both the steady-state and transient characteristics of the HVDC system into account, is proposed. The control strategy under steady states includes two control modes: constant AC voltage control and constant reactive power control. The control strategy under transient states also includes two control modes: fast reactive power droop control and active blocking control. Based on the operating conditions of both the HVDC system and the STATCOM, the decision criterion and the switching control of the STATCOM adopting the specific control strategy are proposed; 3) Aiming at the problem of slow reactive power response in the STATCOM using the traditional maximum reactive power control under transient conditions, a fast reactive power droop control strategy is proposed and a turn-off angle negative feedback control is added. This method can provide reactive power compensation more rapidly under transient conditions and mitigate the occurrence of commutation failures for the HVDC system. A simulation model of the STATCOM integrated HVDC system is established in PSCAD/EMTDC. The effectiveness of the proposed improved coordinated control strategy in enhancing the receiving AC system strength and reducing the probability of commutation failures under transient conditions, is verified by the simulation results.